Proteomic analysis of synaptic protein turnover in the anterior cingulate cortex after nerve injury - Ko, Hyoung-Gon (Mol Brain, 2020)
Synaptic proteins play an important role for the regulation of synaptic plasticity. Numerous studies have identified and revealed individual synaptic protein functions using protein overexpression or deletion. In neuropathic pain nociceptive stimuli conveyed from the periphery repetitively stimulate neurons in the central nerve system, brain and spinal cord. Neuronal activities change the turnover (synthesis and degradation) rate of synaptic proteins. Thus, the analysis of synaptic protein turnover rather than just expression level change is critical for studying the role of synaptic proteins in synaptic plasticity. Here, we analyzed synaptosomal proteome in the anterior cingulate cortex (ACC) to identify protein turnover rate changes caused by peripheral nerve injury. Whereas PKCγ levels were not altered, we found that the protein’s turnover rate decreased after peripheral nerve injury. Our results suggest that postsynaptic PKCγ synthesized by neuronal activities in the ACC is translocated to the postsynaptic membrane with an extended half-life.